Digitalisasi Layanan Administrasi Dan Manajemen BUMDes Melalui Aplikasi Smart Village Di Desa Neglasari Kabupaten Sumedang - Tyastuti Sri Lestari; Ismaniah Ismaniah; Wowon Priatna; Rasim Rasim (Jurnal Pengabdian kepada Masyarakat UBJ, 2026)
Village digitalization is needed not only to simplify administrative services but also to support more accountable management of Village-Owned Enterprises (BUMDes). In Neglasari Village, Sumedang Regency, several administrative services and BUMDes records were still handled manually, which affected service time, data accuracy, and business reporting. This community service program aimed to assist the village in applying a web-based Smart Village application to support digital administration and BUMDes management. The program was carried out through socialization, hands-on training, system implementation, mentoring, and evaluation involving village officers, BUMDes managers, and local MSME actors. The application provides features for online letter requests, population data management, transaction recording, business reporting, and digital promotion of village products. The implementation showed practical benefits for village services and business governance. Administrative service time decreased from 15–20 minutes to 5–7 minutes per request, while recording errors were reduced through more structured digital data management. The system also helped BUMDes managers monitor transactions and prepare business reports more easily. In addition, the training improved participants’ understanding of the system, with an average score of 4.3 out of 5. These results indicate that the Smart Village application can support the digitalization of village administration and strengthen BUMDes management in Neglasari Village